A new species of Plinia (Myrtaceae) from the Bahia Atlantic Forest - Stadnik, Aline; Souza, Marcelo Da Costa; Lucas, Eve; Roque, Nádia (Phytotaxa, 2020)
The Brazilian Atlantic Forest is one of the most diverse biomes in the world. The state of Bahia includes an important portion of the central corridor of Atlantic Forest that runs along the Brazilian coast. Myrtaceae is a dominant family of trees in this biome, and among its genera, Plinia is a genus notable for high number of endangered species in the Bahia Atlantic Forest. Plinia ybotyrype is here described, discussed and illustrated. An identification key for related species is also provided.